2022
DOI: 10.3390/medicina58111692
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Autologous Micrograft and Its Derived Mesenchymal Stem Cells in a Bio Cross-Linked Hyaluronic Acid Scaffold for Correction Deep Wrinkles, Facial Depressions, Scars, Face Dermis and Its Regenerations: A Pilot Study and Cases Report

Abstract: The aim of this clinical study was to demonstrate that through a micrograft of viable adipose tissue cells microfiltered at 50 microns to exclude fibrous shoots and cell debris in a suspension of cross-linked hyaluronic acid, we were able to improve visible imperfections of the dermis and to improve clinically observable wrinkles, with a beneficial effect also in the extracellular matrix (ECM). Background and Objectives: With the passage of time, the aging process begins, resulting in a progressive impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The isolation protocol is based on MACS technology, which enables the rapid isolation of high-purity and high-yield EVs. Through this procedure, it was verified that, despite the final filtration procedure at 0.2 microns (200 nanometers), there were still particles covering part of the characterization signal, but we could see the presence of numerous vesicles using exosomal marker CD81, typical of regenerative functions [51], and the mesenchymal/endothelial marker CD146, specific for ADSCa after stabilization [52] (Figure 4). This ultrafiltration technique made it possible to obtain microvesicles that did not contain almost any of the components of the interfering adipose disaggregate [27,38].…”
Section: Resultsmentioning
confidence: 97%
“…The isolation protocol is based on MACS technology, which enables the rapid isolation of high-purity and high-yield EVs. Through this procedure, it was verified that, despite the final filtration procedure at 0.2 microns (200 nanometers), there were still particles covering part of the characterization signal, but we could see the presence of numerous vesicles using exosomal marker CD81, typical of regenerative functions [51], and the mesenchymal/endothelial marker CD146, specific for ADSCa after stabilization [52] (Figure 4). This ultrafiltration technique made it possible to obtain microvesicles that did not contain almost any of the components of the interfering adipose disaggregate [27,38].…”
Section: Resultsmentioning
confidence: 97%
“…EQ-9 potentially inhibits inflammation through increasing the fibroblast survival rate and decreasing intracellular ROS levels [93]. It has been reported that microfragmented adipose tissue containing adipose stem cells combined with a crosslinked hyaluronic acid scaffold can improve soft tissue defects such as deep wrinkles [94].…”
Section: Applications Of Mesenchymal Stem Cells In Skin Regeneration ...mentioning
confidence: 99%
“…AD-MSCs have shown a multitude of possible applications in clinical research, ranging from liver injury, myocardium and bone reconstruction, nerve regeneration to muscle-skeletal dysfunctions or diabetes [12].…”
Section: Introductionmentioning
confidence: 99%